Adaptação transcultural e busca de evidências de validade da escala de clima escolar Delaware School Survey – Teacher/Staff (DSS-T/S) para o idioma português brasileiro - Strey, Artur Marques (2020)
The Delaware School Survey - Teacher / Staff Instrument (DSS-T/S) was designed and validated to assess the school climate perceived by teachers and staff of the Delaware State’s schools. It was developed along with two other instruments, one for assessing school climate from the perspective of parents and guardians (Delaware Home Survey) and the other from students' perspective (Delaware Student Survey). School climate is the perception of students, family members, teachers and other members of an educational institution about the quality and character of school life, including norms, values and expectations. The development of three different instruments is supported by the importance of crossing different perceptions and also derives from the understanding that measures that evaluate only one or two of the three largest groups that make up the school community (students, parents, and school staff) are less favorable for a complete overview of the process and for qualifying the school climate. Collecting data from multiple respondents enables data and information triangulation. The DSS-T/S consists of two scales: Delaware School Climate Scale - Teachers and Staff (DSCS-T/S) and Positive, Punitive, and Social Emotional Learning Techniques Scale − Teacher/Staff (DTS-T/S). This instrument aims to gather information for needs assessment, program development, program evaluation (particularly bullying prevention programs) and other behavioral problems and to promote social and emotional skills. Objective: The aim of this study was to translate, adapt culturally and investigate evidence of validity of the DSS-T/S in Brazilian Portuguese. Method: The study had a sample of 180 respondents, with 67,7% of women and 32,3% of men. The sample included teachers, managers, educational counselors, school supervisors, and other school staff from private or public schools, as well as eight technical schools. Primarily, the original instrument was translated into Portuguese by two translators whose native language is Portuguese and fluent in English, resident in Brazil and with previous experience in psychological instrument translation. A synthesis of the two translations was performed by a third independent translator, also fluent in English, having Portuguese as his native language and with previous experience in psychological instruments translation. After this, a pilot evaluation of the scale items was carried out with seventeen teachers from a private school in Porto Alegre. Teachers were asked to comment on items they thought needed modification. After further adjustments, the scales were sent to a committee of three experts in the field of School Psychology for language clarity, theoretical relevance and practical relevance of the items. Through the analysis of the assessments, a final semantic adjustment was made by the translation team based on the expert committee's responses. Then, the reverse translation of the Portuguese version into English was prepared by a fourth independent translator, fluent in Portuguese and with a broad mastery of the English language. Reverse translation was submitted to the original author to ensure content equivalence. After evaluation and approval of the project by the Ethics Committee, the instruments were collected online through the Qualtrics website, from a convenience and snowball sample. A non-online data collection was also held at public and private schools in Porto Alegre, as well as an online data collection on eight technical education schools. To account for the objectives of this study, descriptive statistics techniques were used. Cronbach's alphas were calculated to verify the internal consistency of the general instrument and subscales. Correlations between the parts of the instrument were also calculated. Exploratory and confirmatory factor analysis of the DSST/S were performed. In compliance with the Guidelines and Regulatory Standards involving research with human beings provided for in Resolution No. 510 of the National Health Council (2016), Resolution No. 466 of December 12, 2012 and Resolution No. 016/2000 of the Federal Council of Psychology (2000), this research protects the necessary ethical care. This research was approved by the Ethics Committee of the Pontifical Catholic University of Rio Grande do Sul (PUCRS) under the number CAAE: 10949419.9.0000.5336. Results: The scales showed good internal consistency, with Cronbach's alpha of 0.93 for DSCS-T/S and 0.75 for DTS-T/S. The Kaiser-Meyer-Olkin measure verified the sample adequacy for the analysis (KMO = 0.912 for DSCS-T / S and KMO = 0.819 for DTS-T / S). Bartlett's sphericity test (approximate chi-square: 4973.67; significance level of 0.000 [DSCS-T / S] and approximate chi-square: 1307.736; significance level of 0.000 [DTS-T / S]), indicated that the correlations between the items are enough to carry out the analysis. A Principal Component Analysis (PCA) was conducted on the 39 items of the DSCS-T / S and the 16 items of the DTS-T / S with orthogonal rotation (varimax), with initial analysis showing eight components for the DSCS-T / S and three components for DTS-T / S that followed the Kaiser criterion of eigenvalue greater than 1.0 and explained 69.938% of the variance in the DSCS-T / S and 59.725% of the variance in the DTS-T / S. Confirmatory Factor Analysis was used to test the models suggested in the PCA, with eight components in the DSCS-T / S and the threecomponent model of the DTS-T / S, and fixing the models proposed in the American versions, of nine factors for DSCE-T / S and three factors for DTS-T / S. Comparing the models, the results showed the model proposed by the original authors presented better values (DSCS - TLI: 0.849; CFI: 0.866; RMSEA: 0.072; DTS - TLI: 0.813; CFI: 0.842; RMSEA: 0.104) than the PCA model (DSCS - TLI: 0.818; CFI: 0.834; RMSEA: 0.08; DTS - TLI: 0.841; CFI: 0.866; RMSEA: 0.096). Discussion: The results showed that the scales had adequate internal consistency, corroborating the original authors findings (Bear et al., 2016). From the results of the Confirmatory Factor Analyzes, it was possible to identify that the factorial model of the empirical structure based on the authoritative discipline (Baumrind, 1996) and the theoretical framework of Stockard and Mayberry (1992) is more adequate than the model raised by the PCA. The factorial model based on this theoretical framework was also adopted in the student version of the Delaware School Survey for use in Brazil (Bear, Holst, Lisboa, Yang & Chen, 2016). With this, it is possible to triangulate data from the three scales, allowing a more global and qualified analysis of the school climate. With the most accurate assessment, interventional actions can be implemented in a more strategic way, aiming at greater impact. The scales can still be used to reassess these interventions, seeking continuous improvement. Conclusion: The translation, adaptation and validation process of the Delaware School Survey - Teacher/Staff (DSS-T / S) presented content validity evidence, good internal consistency and good factorial structure, proving to be suitable for use in the Brazilian population. The instrument contributes to the assessment of the school climate by different groups: teachers and school staff. The limitations of this study include the sample size and the limitation of the region covered by the data collection. Future studies may include network analysis and replication of validation analyzes, so that the consistency of the instrument can be reinforced, as well as studies may include the three scales for assessing the school climate. The data that can be obtained through the use of the scale can provide subsidies to managers, researchers and public policy makers to identify relevant intervention points in order to provide support to these groups, in addition to facilitating the inclusion of these professionals in the process of changing the school context (La Salle, Neves, Freeman, & Sugai, 2019).